The Influence of Family Environment on Islamic Education Learning Achievement of Elementary School Students in Pagandon Village - Nuruddin Arraniri; Agus Asri sabana; Fadilatul Khoirunnisa (Departement of PAI, Universitas Majalengka, 2026)
This study investigates the influence of the family environment on the Islamic Religious Education (PAI) learning achievement of elementary school students in Pagandon Village. The family environment, as the first and primary educational setting, is believed to significantly shape children’s academic performance through parenting patterns, emotional support, and socio-economic conditions. This research employed a quantitative approach with a deductive method. Data were collected through observations, questionnaires, and interviews, with a sample of 81 parents, representing 25% of the total population. The data were analyzed statistically using the SPSS program, including validity, reliability, correlation, and simple linear regression tests. The findings reveal a positive and significant correlation between the family environment and students’ PAI achievement. The Spearman correlation test confirmed that supportive family environments—characterized by active parental involvement, consistent communication, and religious home practices—tend to enhance students’ academic performance. Regression analysis further indicated that the family environment contributes meaningfully to variations in learning achievement, with a significance value below 0.05. These results highlight the critical role of the family as the foundation of children’s education. Strengthening parental involvement, maintaining harmonious interactions, and fostering religious values at home are recommended strategies to improve students’ performance in Islamic Religious Education. This study not only provides empirical evidence for the importance of family factors in